The German Public Finances in the COVID-19 Pandemic - Heinz Gebhardt; Lars-H. Siemers (Wirtschaftsdienst)
Abstract The general government budgetary position of Germany at the beginning of the coronavirus crisis is advantageous due to extremely favourable conditions of the 2010s. Since 2012, surpluses prevailed, and in 2019 the public debt ratio decreased below 60%. The coronavirus crisis ends this success story dramatically and causes a historically high deficit as well as a rise in the debt ratio to about 77.5% in 2020. This requires consolidating the budget, mainly because age related spending will rise significantly and because an interest rate reversal may involve additional interest payments in the future. To ensure long term debt sustainability, restricting primary expenditures is imperative.